2021
DOI: 10.1088/1361-648x/ac2b68
|View full text |Cite
|
Sign up to set email alerts
|

Protected quantum coherence by gain and loss in a noisy quantum kicked rotor

Abstract: We study the effects of non-Hermiticity on quantum coherence via a noisy quantum kicked rotor (NQKR). The random noise comes from the fluctuations in kick amplitude at each time. The non-Hermitian driving indicates the imaginary kicking potential, representing the environment-induced atom gain and loss. In the absence of gain and loss, the random noise destroys quantum coherence manifesting dynamical localization, which leads to classical diffusion. Interestingly, in the presence of non-Hermitian kicking poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…[47][48][49] Recently, the extension of Floquet synthetic systems to non-Hermitian regime enables the investigations on novel physics that might not be easily achievable in Hermitian settings. It is found that the combination of non-Hermiticity and nonlinear interaction leads to superexponentially fast energy diffusion, [50] the non-Hermitian driven potential enhances the degree of DL [51][52][53][54] and induces the quantum criticality of information scrambling. [55] The versatile nature of Floquet synthetic systems opens the opportunity for exploring diverse regimes of quantum behavior by tailoring system parameters and controlling interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Recently, the extension of Floquet synthetic systems to non-Hermitian regime enables the investigations on novel physics that might not be easily achievable in Hermitian settings. It is found that the combination of non-Hermiticity and nonlinear interaction leads to superexponentially fast energy diffusion, [50] the non-Hermitian driven potential enhances the degree of DL [51][52][53][54] and induces the quantum criticality of information scrambling. [55] The versatile nature of Floquet synthetic systems opens the opportunity for exploring diverse regimes of quantum behavior by tailoring system parameters and controlling interactions.…”
Section: Introductionmentioning
confidence: 99%